1995
DOI: 10.1177/016235329401800102
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Behavior Problems among Elementary School Students in Gifted Programs

Abstract: This report summarizes a comparison of 675 gifted and 322 regular education students (grades 2 or 3) on the incidence of behavior problems as rated b y parents using the Achenbach Child Behavior Checklist (CBCL) and b y teachers using the Teacher Report Form of the CBCL. After controlling for grade and minority status, there were n o significant differences between gifted and regular education students in the incidence of any form of behavior problems as rated b y either teachers or parents. The small group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
(19 reference statements)
2
20
0
Order By: Relevance
“…The findings of the present study are consistent with previous empirical research indicating fewer gifted children demonstrate emotional and behavioral risk than their nongifted counterparts (Cornell et al, 1994;Gallucci et al, 1999;Garland & Zigler, 1999). Using a multi-informant, multigate approach highlighted important differences between par ent and teacher ratings.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the present study are consistent with previous empirical research indicating fewer gifted children demonstrate emotional and behavioral risk than their nongifted counterparts (Cornell et al, 1994;Gallucci et al, 1999;Garland & Zigler, 1999). Using a multi-informant, multigate approach highlighted important differences between par ent and teacher ratings.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Garland and Zigler (1999) found that adolescents participating in a summer camp for gifted students scored within typical ranges in the Child Behavior Checklist (a standardized measure of social and emotional problems; Achenbach, 1991) according to the national norms. Cornell, Delcourt, Bland, Goldberg, and Oram (1994) reported similar results using the same instrument with elementary-school gifted children and a comparison group of average-ability children. After controlling for the effects of educational level and minority status, they found no significant differences between both groups concerning the incidence of any type of behavioral problems as reported by their parents and teachers.…”
Section: Giftedness As a Protective Factor: The Resilience Approachmentioning
confidence: 59%
“…Moreover, a common frame of reference was established and this facilitated communication about the child (cf. Cornell, Delcourt, Bland, Goldberg, & Oram, 1994). The outcomes per domain were also used to plan further educational support for each child in the form of specific play or diagnostic and learning activities and corresponding instructional lines.…”
Section: Implementation and Further Development In Practicementioning
confidence: 99%